Antibacterial Activities of Methanol and Aqueous Extracts of Salvadora persica against Streptococcus mutans Biofilms: An In Vitro Study - Abdulrahman A. Balhaddad; Lamia Mokeem; Mary Anne S. Melo; Richard L. Gregory (MDPI AG, 2021)
The use of herbal products in oral hygiene care has a long history, and their use is popular today. A tree stick, named Salvadora persica (S. persica), is commonly used to remove dental plaque and clean teeth in many countries. In addition, extracts of S. persica can be used as a mouthwash, as they demonstrate antimicrobial properties. This study aimed to investigate the antibacterial effect of S. persica methanol and aqueous extracts against Streptococcus mutans (S. mutans) biofilm. A S. mutans biofilm formation assay was conducted using different concentrations of S. persica methanol or water extracts in tryptic soy broth (TSB) supplemented with 1% sucrose. The biofilm was stained with crystal violet dye, and the absorbance was assessed to examine biofilm formation. One-way analysis of variance (ANOVA) and Tukey tests were used to analyze the results. The S. persica methanol extract displayed a significant inhibition (p ≤ 0.001) against the S. mutans biofilm. The 10 mg/mL concentration of the S. persica methanol extract was determined as the minimum biofilm inhibitory concentration (MBIC). The used methanol concentration, mixed with TSB supplemented with 1% sucrose and without the S. persica extract, did not inhibit the S. mutans biofilm. The S. persica aqueous extract did not demonstrate any biofilm inhibition at any concentration (p ≥ 0.05). The findings of this study suggest the potential of using S. persica methanol extract as a mouthwash or adjunctive to oral hygiene tools.